DEVELOPMENT OF THE 6Cs EMERGENCE MEASUREMENT INSTRUMENTS IN ELEMENTARY SCHOOLS - Poppy Anggraeni; Dadang Sunendar; Bunyamin Maftuh; Wahyu Sopandi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The instrument for measuring the emergence of 6Cs in learning at elementary schools is an instrument developed to measure the emergence of character, critical thinking, creativity, citizenship, collaboration, and communication in learning planning and learning implementation at elementary schools. The purpose of the research in this paper is to analyze the instrument validity that has been developed to measure the emergence of 6Cs in learning planning and implementation at elementary schools and to describe the copyrighting of a validated instrument. The research method uses the Research and Development of the ADDIE model, which consists of analyzing, designing, developing, implementing, and evaluating stages. Instrument validation was carried out by four experts. Instruments that have been validated were subsequently revised based on the suggestions for improvement and calculated the validity percentage and validity level. The results indicate that the instrument for measuring the emergence of 6Cs in learning planning at elementary schools had a validity percentage of 97.74% with a very valid validity level. The instrument for measuring the emergence of 6Cs in learning implementation at elementary schools had a validity percentage of 94.41% with a level very valid validity likewise. The results of the validation and this instrument copyright can be a reference to measure the quality of learning planning and implementation so that it can improve the learning quality in elementary schools, especially related to the learning that can facilitate the development of 6Cs.